2014
DOI: 10.1016/j.meegid.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of Leishmania species based on trypanosomatid barcode (SSU rDNA) and gGAPDH genes: Taxonomic revision of Leishmania (L.) infantum chagasi in South America

Abstract: Phylogenetic studies on trypanosomatid barcode using V7V8 SSU rRNA and gGAPDH gene sequences have provided support for redefining some trypanosomatid species and positioning new isolates. The genus Leishmania is a slow evolving monophyletic group and including important human pathogens. The phylogenetic relationships of this genus have been determined by the natural history of its vertebrate hosts, vector specificity, clinical manifestations, geographical distribution and molecular approaches using different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 82 publications
2
51
0
16
Order By: Relevance
“…The Leishmania infantum chagasi (CBT56 -Coleção Brasileira de Tripanossomatídeos FMVZ/USP) sample was isolated from a popliteal lymph node from a naturally infected dog in the city of Cuiabá, and was characterized using molecular methods 18 . The L. amazonensis strain IFLA/BR/1967/PH8 was obtained courtesy of the Leishmaniasis Research Laboratory, Oswaldo Cruz Foundation, and forms part of the Oswaldo Cruz Institute's Leishmania Collection.…”
Section: Indirect Fluorescent Antibody Testmentioning
confidence: 99%
“…The Leishmania infantum chagasi (CBT56 -Coleção Brasileira de Tripanossomatídeos FMVZ/USP) sample was isolated from a popliteal lymph node from a naturally infected dog in the city of Cuiabá, and was characterized using molecular methods 18 . The L. amazonensis strain IFLA/BR/1967/PH8 was obtained courtesy of the Leishmaniasis Research Laboratory, Oswaldo Cruz Foundation, and forms part of the Oswaldo Cruz Institute's Leishmania Collection.…”
Section: Indirect Fluorescent Antibody Testmentioning
confidence: 99%
“…BM and PB parasite isolation was generally obtained at the same day, except for one patient with BM being positive at day 10 and PB at day 20, probably due to increased amount of parasites in the former. L. infantum specificity of all isolates was confirmed by Sanger's sequencing of the V7V8 variable segment of trypanosomatides 18S rRNA encoding gene, as previously described [11] [GenBank: KT762389-KT762398]. L. i. chagasi negative patients presented hematologic alterations related to VL clinic and laboratorial characteristics, whose discussion is out of this report proposal.…”
Section: The Studymentioning
confidence: 89%
“…Visceral leishmaniasis in the Americas is caused by the species L. infantum chagasi that is phylogenetically distinct from other species of the L. donovani complex [18]. Recent study showed that the V7V8 SSU rDNA region segregated all species of the genus Leishmania and can be used for barcode as in other genera of trypanosomatids.…”
Section: Discussionmentioning
confidence: 99%
“…The aspirates contents were inoculated into Vacutainer tubes containing a biphasic medium consisting of 15% sheep red blood cells as the solid phase (blood agar base), overlain by liquid LIT medium supplemented with 20% Fetal Bovine Serum [18].The culture was incubated at 28°C and grown in LIT medium for DNA preparation.The isolates were cryopreserved in liquid nitrogen in the Brazilian Trypanosomatid Collection (Coleção Brasileira de Tripanossomatídeos, CBT), in the Department of Preventive Veterinary Medicine and Animal Health, School of Veterinary Medicine, University of São Paulo, Brazil.…”
Section: Isolation Of Leishmaniamentioning
confidence: 99%
See 1 more Smart Citation